2018
DOI: 10.4037/ajcc2018615
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Saline Instilled During Endotracheal Suction in Pediatric Intensive Care: A Randomized Trial

Abstract: Background Saline instillation is still used to assist in removal of secretions from endotracheal tubes in some pediatric intensive care units. Objective To compare the effect of using either no saline, quarter-normal (0.225%) saline, or normal (0.9%) saline during endotracheal suctioning of children receiving ventilatory support in a pediatric intensive care unit. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…66 Normal saline solution use during artificial airway suctioning has also been shown to increase dyspnea in patients $ 60 years of age. 73 McKinley et al 74 performed a randomized trial to evaluate the hours of intubation and invasive mechanical ventilation in pediatric subjects. They found that using no saline solution was as effective as using quarter-normal or normal saline solution.…”
Section: Normal Saline Solution Lavage For Artificial Airway Suctioningmentioning
confidence: 99%
See 1 more Smart Citation
“…66 Normal saline solution use during artificial airway suctioning has also been shown to increase dyspnea in patients $ 60 years of age. 73 McKinley et al 74 performed a randomized trial to evaluate the hours of intubation and invasive mechanical ventilation in pediatric subjects. They found that using no saline solution was as effective as using quarter-normal or normal saline solution.…”
Section: Normal Saline Solution Lavage For Artificial Airway Suctioningmentioning
confidence: 99%
“…They found that using no saline solution was as effective as using quarter-normal or normal saline solution. 74 In a prospective observational study, Owen et al 71 noted more adverse events in pediatric subjects who received normal saline solution during suctioning events. A randomized clinical trial by Caruso et al 75 noted a decrease in microbiologically proven VAP with the use of normal saline solution during artificial airway suctioning.…”
Section: Normal Saline Solution Lavage For Artificial Airway Suctioningmentioning
confidence: 99%
“…Isotonic saline has been used to clear secretions from the endotracheal tube; however, there are considerations for harm. In intubated children, not specifically with PARDS, McKinley et al (49) randomized 427 to one of three endotracheal suctioning treatment groups: no saline, 0.2% saline, and 0.9% saline instillation. No saline use was just as effective as either saline instillation.…”
Section: Resultsmentioning
confidence: 99%
“…Disappointingly, few randomized controlled studies have so far studied the effectiveness of mucoactive agents during invasive mechanical ventilation in an either specific or general PICU population. McKinley et al have investigated the effect of no saline versus 0.225% or 0.9% saline installation before routine endotracheal suction to remove phlegm in 427 children receiving ventilator support [102]. However, in this non-blinded trial, no statistically significant differences in duration of mechanical ventilation, oxygen therapy or PICU stay between the groups were found.…”
Section: Pediatric Critical Care: Mechanically Ventilated Childrenmentioning
confidence: 98%